A Muslim Reflects on Christ Crucified: Stumbling-Block or Blessing? - Roberts, Nancy (Islam and Christian-Muslim relations, 2013)
The aim of this article is to encourage Muslim readers to consider the possibility of seeing the crucifixion as an actual historical event whose occurrence can be affirmed on the basis of qur'anic teachings. Following a description of the difficulty that arises for someone with a Christian mindset who encounters the qur'anic denial (or seeming denial) of the crucifixion, given its centrality to the Christian message, the article summarizes qur'anic exegeses that allow for an affirmation of the crucifixion based on Q 4.157-158. This is followed by discussions of: the relevance of the crucifixion to the human condition; the factors that have contributed to a denial of the crucifixion based on Q 4.157-8; Christian and Islamic themes that have the potential to facilitate a view from within Islam of Christ's death as redemptive; and what Christ's death may be seen to reveal about the divine nature. Lastly, the article presents ways in which Christians down the ages have experienced the crucifixion and resurrection as events and as symbols, and as an inspiration for service and the love of God.